A DFT study of the electronic, optical and topological properties of free and biaxially strained CuIn1−xAlxSe2. Issue 19 (29th April 2019) - Jiang, Pingping; Boulet, Pascal; Record, Marie-Christine
Abstract : Among the CuIn1− x Al x Se2 alloys, that with x = 0.25 is the optimal one in terms of band gap and conversion efficiency. Its absorption coefficient is highly modified under biaxial strains that occur in thin films. Abstract : The electronic and optical properties of free and biaxially strained CuIn1− x Al x Se2 were calculated by using the full potential linear augmented plane wave (FP-LAPW) method. The results show that CuIn1− x Al x Se2 has a direct band gap with increasing value as x increases. CuIn0.75 Al0.25 Se2 has been recognized as the optimally substituted compound in terms of band gap and conversion efficiency. The geometry optimized bond length and bond angle between nuclei terminal atoms (M and Se) and the bond critical point, the electron density ρ, the local energy density, and Laplacian ∇ 2 ρ for nonequivalent pairwise M–Se were examined. High bond deflection with a small bond angle provides a high possibility of electron transition, which mainly occurs between In and Se orbitals. Under biaxial strains, the optical properties are improved along the lengthened deformation direction.